2012
DOI: 10.1186/1471-2474-13-167
|View full text |Cite
|
Sign up to set email alerts
|

Conservative treatment, plate fixation, or prosthesis for proximal humeral fracture. A prospective randomized study

Abstract: BackgroundProximal humerus fracture is the third most common fracture type after hip and distal radius fracture in elderly patients. A comprehensive study by Palvanen et al. demonstrated an increase in the annual fracture rate of 13.7% per year over the past 33 years. Should this trend continue, the fracture rate would triple over the next three decades. The increasing incidence of low-energy fractures raises questions about the optimal treatment in terms of functional outcome, pain, and rehabilitation time, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 26 publications
0
49
0
3
Order By: Relevance
“…The number of upper extremity fragility fractures will continue to increase as the US population continues to age, and the impact these fractures have on our health care system and patient quality of life will become a greater burden. Distal radius and proximal humerus fractures (PHF) are common among the elderly population as they are the second and third most common fractures in adults over the age of 65 [8]. It is estimated that proximal humerus fractures account for 20 % of all osteoporotic fractures, and it has been reported that more than 70 % of proximal humeral fractures occur in patients over 60 years old [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The number of upper extremity fragility fractures will continue to increase as the US population continues to age, and the impact these fractures have on our health care system and patient quality of life will become a greater burden. Distal radius and proximal humerus fractures (PHF) are common among the elderly population as they are the second and third most common fractures in adults over the age of 65 [8]. It is estimated that proximal humerus fractures account for 20 % of all osteoporotic fractures, and it has been reported that more than 70 % of proximal humeral fractures occur in patients over 60 years old [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In total, HH identified one new single-centre RCT, 95 which compared hemiarthroplasty with non-surgical treatment in 50 patients, and a published protocol for an ongoing trial [Treatment of Proximal Humeral Fractures (TPHF)]. 96 Brief details of the eight RCTs now available on this topic are provided in Table 89. …”
Section: Summary Review Of the Currently Available Evidencementioning
confidence: 99%
“…The strategy reduces the risk of influence of subjective expectations, which may influence the results [44]. By the same reason, the statistician and the researchers evaluating the study will be blinded for which treatment the three group of patients have received until the results are interpreted and consensus is reached.…”
Section: Study Designsmentioning
confidence: 99%
“…Therefore, a prospective study without control group is in general considered to represent a low level of evidence [44]. The inclusion of a control group will improve the evidence, but groups may be different and bias results.…”
Section: Background For the Current Studymentioning
confidence: 99%
See 1 more Smart Citation